2012
DOI: 10.2528/pier11121101
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Image Formation Algorithm for High-Resolution Wide-Swath Spaceborne Sar Using Compressed Sensing on Azimuth Displacement Phase Center Antenna

Abstract: Abstract-High-resolution wide-swath (HRWS) imaging with spaceborne synthetic aperture radar (SAR) can be achieved by using azimuth displacement phase center antenna (DPCA) technique. However, it will consequently leads to extremely high data rate on satellite downlink system. A novel sparse sampling scheme based on compressed sensing (CS) theory for azimuth DPCA SAR was proposed, by which only a small proportion of radar echoes are utilized for imaging to reduce data rate. The corresponding image formation alg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 23 publications
(41 reference statements)
0
33
0
Order By: Relevance
“…A great deal of compressed sensing based methods have been applied to radar systems [8][9][10][11][12][13][14][15][16][17][18], which recover the target scene from fewer measurements than traditional methods. In [8], it is demonstrated that the compressed sensing can eliminate the need for matched filter at the receiver and has the potential to reduce the required sampling rate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A great deal of compressed sensing based methods have been applied to radar systems [8][9][10][11][12][13][14][15][16][17][18], which recover the target scene from fewer measurements than traditional methods. In [8], it is demonstrated that the compressed sensing can eliminate the need for matched filter at the receiver and has the potential to reduce the required sampling rate.…”
Section: Introductionmentioning
confidence: 99%
“…[10] focuses on monostatic chaotic multiple-input-multiple-output (MIMO) radar systems and analyze theoretically and numerically the performance of sparsity-exploiting algorithms for the parameter estimation of targets at Low-SNR. In the context of synthetic aperture radar (SAR), [11][12][13][14][15][16] present compressed sensing based data acquisition and imaging algorithms. An additional sensing matrix H is introduced in [17,18], which compress the received signal further by making nonadaptive, linear projections of the direct data sampled at the Nyquist frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic aperture radar (SAR) is a microwave sensor which has the ability to produce all-weather, 24-hour a day, high-resolution images [1,2]. A SAR system sends electromagnetic pulses from a radar mounted on an airborne or spaceborne platform to a particular area of interest on the ground and records the return signals.…”
Section: Introductionmentioning
confidence: 99%
“…The spaceborne synthetic aperture radar (SAR) systems have attracted special interest in remote sensing tasks due to its high resolution [1,2], day/night operations, weather insensitivity and global coverage. Recently, SAR systems have been employed for environmental monitoring [3], surveillance [4,5], target identification [6], public security [7], navigation [8] and target recognition [9].…”
Section: Introductionmentioning
confidence: 99%